Cerebellar metastasis from colorectal cancer: a case report - Angulo-Rojo, Carla E.; Castillo-Gaxiola, Luis J.; Gaxiola-Gastélum, Karen; Guadrón-Llanos, Alma M.; Magaña-Gómez, Javier A.; Baldenebro-Félix, Diana L. (Frontiers in Oncology, 2025)
IntroductionColorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide, with adenocarcinoma as the most common subtype. While metastasis typically occurs in the liver, lungs, and peritoneal cavity, metastasis to the brain, particularly the cerebellum, is exceedingly rare.Case presentationThis report discusses the case of a 50-year-old woman diagnosed with mucinous adenocarcinoma of the descending colon. Over six years, the patient experienced multiple common metastatic sites, including the liver and lungs, before developing a rare cerebellar metastasis. Despite extensive treatment, including surgery and chemotherapy, the disease progressed, ultimately leading to the patient’s demise. This case represents the first documented cerebellar metastasis from CRC in Mexico.ConclusionThis case highlights the altered metastatic patterns in CRC due to advanced therapies that extend survival. Clinicians should remain vigilant for metastasis to uncommon sites, such as the cerebellum, especially in patients with prolonged survival. Further research is needed to understand the mechanisms underlying such metastatic behavior and optimize treatment strategies.